Remote technologies in critical infrastructure drone operator training - Zhyhir, Victoriia; Onyshchenko, Serhii (DEL c.z., 2024)
Modern remote technologies make it possible to act effectively without risk and losses, but at the same time they undermine the social legitimacy and authority of those norms of military ethics, which the military has traditionally followed throughout the history of mankind.